Pengaruh Strategi Pembelajaran Index Card Match DanStudent Team Achivement Division (Stad) Terhadap HasilBelajar Matematika Ditinjau Dari Motivasi Belajar Siswa Kelas XI IPS Semester Ganjil Di SMA Negeri 2 Sukoharjo Tahun 2016/2017 - Melati Putri, Fitria, Drs. Slamet HW, M.Pd (2016)
This research aim to know, (1) influence of usage of strategy of Index Card Match and of Student Team Achievement Division (STAD) to result learn mathematics, (2) influence of motivation learn student to result learn mathematics, (3) interaction between usage of study strategy of Index Card Match and of Student Team Achievement Division (STAD) and also motivate to learn to result learn student mathematics. This population of research is entire class student of XI IPS anomalous semester in SMA Negeri 2 Sukoharjo. Samples in this research use two classes, which is experiment class hit by strategy of Index Card Match and control class hit by strategy of Student Team Achievement Division (STAD). The technique intake of sample conducted with technique of cluster sampling random. In this research, researcher use method of test, documentation and questioner. In this research is used by hypothesis test with analysis of variance two way with cell do not be is same. Before to analyses of variance, to do test prerequisite analyses by using method of Liliefors for the test of normality, and use test of Barlet for the test of homogeneity. Result of calculation of data analysis by using level of significance 5% obtained; (1) there are difference of result learn mathematics between given by student is treatment by using approach integrated at method of Index Card Match and method of Student Team Achievement Division (STAD)with Fα = 5,333 > F0,05;1;61 = 4,007, (2) there are difference of result learn student mathematics evaluated from motivational level learn student with high category, medium category, and lower category, with Fb = 6,871 > F0,05;2;61 = 3,156 and (3) there is no interaction between method of Index Card Match and method of Student Team Achievement Division (STAD) evaluated from motivation learn student to result learn student with FAB = 3,068 > F0,05;2;61 = 3,148.